Transmission Performance Analysis of TDMA Radio and MAC Communication of TDMA Protocol. (February 2019) - Nando, Ferry; Permatasari, A; Lindawati,; Handayani, A S; Sitompul, C R; Putri, Hani M
Abstract: Radio is one of the wireless network system devices that is still widely used today. Transceiver was used because the radio can function as a transmitter and receiver. In this paper, half-wave dipole antenna for radio communication as a transceiver on TDMA Digital Radio was simulated. The antenna was used at 167.5 MHz and radio communication channel. In collecting the data, spectrum analyzer was used as the measuring tool. To analyze the output signal generated by TDMA Digital Radio, the data sample on both measurements. This paper compared the TDMA Digital Radio communication with simulation by using MATLAB. Analyze the Channel Power that has become the output of Spectrum Analyzer, and the measurement of Spectrum Analyzer Measurement was using MATLAB.